Almost periodic solutions of evolution equations - Ponomarev, Sergey; Couchouron, Jean-Franҫois; Kamenskiĭ, Mikhail I. (Topological Methods in Nonlinear Analysis, 2017)
We state existence theorems for almost periodic solutions of evolution problems,namely, quasi-autonomous problems and more generally, time dependentevolution equations. We apply these theorems firstly, toa boundary value quasilinear hyperbolic equation of first order, and secondly, to a boundary value quasi-parabolic equation.